Segment-specific patterns of regional lymph-node metastasis in primary small-cell carcinoma of the esophagus: A systematic review and meta-analysis - Ke-Xun Li; Jie Mao; Jian-Zhe Zhang; Zi-Long Qian; Yong-Tao Han; Xue-Feng Leng (World Journal of Clinical Oncology, 2026)
BACKGROUND Primary small-cell carcinoma of the esophagus (SCCE) is a rare, biologically aggressive malignancy with a marked propensity for lymphatic dissemination. We estimated the prevalence of pathologically confirmed lymph-node metastasis in surgically staged SCCE and mapped the available segment-specific evidence at the nodal-station level. AIM To estimate the patient-level prevalence of pathologic lymph-node metastasis in surgically staged SCCE and to map the available segment-specific evidence at the station level. METHODS We conducted a PRISMA-informed exploratory systematic review and meta-analysis of a deduplicated evidence set comprising 99 SCCE-related records. Records were classified as direct nodal-station evidence, cohort-level N-status or prognostic evidence, or contextual case-based/background evidence. Surgically staged cohorts reporting SCCE-specific pathologic nodal positivity, including the CHiSCEC multicenter preprint, were pooled using logit-transformed proportions and a random-effects model. Because station denominators, nodal maps, and reporting definitions were insufficiently compatible for station-by-segment pooling, station-level findings were summarized as an evidence map. RESULTS Four surgical cohorts with compatible pathologic nodal denominators included 579 patients, of whom 352 were node-positive. The pooled prevalence of pathologic lymph-node metastasis was 61.1% (95%CI: 51.4% to 70.0%; I 2 = 76.4%; τ 2 = 0.113), indicating frequent nodal involvement and substantial between-study heterogeneity. CONCLUSION SCCE is associated with a high regional nodal burden, with a pooled prevalence of pathologic nodal metastasis of approximately 61%. Available station-level evidence suggests predominant recurrent laryngeal nerve and upper mediastinal involvement in upper thoracic SCCE, bidirectional spread in middle thoracic SCCE, and predominant perigastric and abdominal involvement in lower thoracic SCCE.